The combustion of lemon peel oil/gasoline blends in spark ignition engine with high-insulation piston crown coating - C. G. Saravanan; Edwin Geo Varuvel; M. Vikneswaran; J. S. Femilda Josephin; Arunachalam Chinnathambi; Arivalagan Pugazhendhi; Haiter Lenin Allasi (Scientific Reports)
Abstract This study explored the recovery of oil from lemon peel biomass and then tested it in a spark ignition as a substitute for gasoline. The study adopted the micro-arc oxidation coating technique, intending to improve the engine performance of the lemon peel oil-gasoline blends. The oil was recovered from discarded lemon peel biomass using steam distillation and then tested in the engine as a fuel by blending it with gasoline at volume ratios of 10, 20, and 30%. An endoscopic visualization approach was employed in this research work to assess the combustion initiation and flame characteristics of gasoline and lemon peel oil blends under different test conditions. Compared to gasoline and blends comprising 20 and 30% lemon peel oil, the 10% lemon peel oil mix produced higher thermal efficiency and lower emissions. The optical analysis demonstrated that premixed combustion with the 10% blend was found to be the highest, resulting in improved combustion and subsequently increased cylinder pressure. To improve the engine performance of the lemon peel oil blends with higher substitution (20 and 30%), the piston was coated with a ceramic coating. A novel technique, namely the micro-arc oxidation technique, was utilized for the coating. The coated piston engine fueled with a 20% lemon peel oil blend showed a 3% and 4.69% increase in thermal efficiency compared to the uncoated piston fueled with a 20% blend and sole gasoline, respectively. The hydrocarbon and carbon monoxide emissions of the engine with a coated piston fueled by the 20% lemon peel oil blend were reduced by 12.7% and 12%, respectively, as compared to gasoline operation in the engine with an uncoated piston.